Strategic innovative marketing : 5th IC-SIM, Athens, Greece 2016 - Kavoura, Androniki; Sakas, Damianos P.; Tomaras, Petros (Springer International Publishing : Imprint : Springer, 2017)
This proceedings volume presents the latest on the theoretical approach of the contemporary issues evolved in strategic marketing and the integration of theory and practice. It highlights strategic research and innovative activities in marketing. The contributed chapters are concerned with using modern qualitative and quantitative techniques based on information technology used to manage and analyze business data, to discover hidden knowledge and to introduce intelligence into marketing processes. This allows for a focus on innovative applications in all aspects of marketing, of computerized technologies related to data analytics, predictive analytics and modeling, business intelligence and knowledge engineering, in order to demonstrate new ways of uncovering hidden knowledge and supporting marketing decisions with evidence-based intelligent tools. The chapters from the proceedings of the 5th International Conference on Strategic Innovative Marketing 2016 cover areas such as social media marketing innovation, sustainable marketing, customer satisfaction strategies, customer relationship management, marketing research and analytics. The papers have been written by scientists, researchers, practitioners and students that demonstrate a special orientation in strategic marketing, all of whom aspire to be ahead of the curve based on the pillars of innovation. This proceedings volume shares their recent contributions to the field and showcases their exchange of insights on strategic issues in the science of innovation marketing.
Keywords: Marketing -- Congresses.; Marketing -- Decision making -- Congresses.; Marketing -- Management -- Congresses.; Information technology.; Business -- Data processing.; elektronické knihy; electronic books